Nano-Mediated Photodynamic Therapy for Cancer: Enhancement of Cancer Specificity and Therapeutic Effects - Ivan Mfouo Tynga (Nanomaterials, 2018)
Deregulation of cell growth and development lead to cancer, a severe condition that claims millions of lives worldwide. Targeted or selective approaches used during cancer treatment determine the efficacy and outcome of the therapy. In order to enhance specificity and targeting and obtain better treatment options for cancer, novel modalities are currently under development. Photodynamic therapy has the potential to eradicate cancer, and combination therapy would yield even greater outcomes. Nanomedicine-aided cancer therapy shows enhanced specificity for cancer cells and minimal side-effects coupled with effective cancer destruction both in vitro and in vivo. Nanocarriers used in drug-delivery systems are very capable of penetrating the cancer stem cell niche, simultaneously killing cancer cells and eradicating drug-resistant cancer stem cells, yielding therapeutic efficiency of up to 100-fold against drug-resistant cancer in comparison with free drugs. Safety precautions should be considered when using nano-mediated therapy as the effects of extended exposure to biological environments are still to be determined.